Development of patient‐specific molecular imaging phantoms using a 3D printer. Issue 8 (30th November 2016) - Gear, J. I.; Long, C.; Rushforth, D.; Chittenden, S. J.; Cummings, C.; Flux, G. D.
Abstract : Purpose: The aim of the study was to investigate rapid prototyping technology for the production of patient‐specific, cost‐effective liquid fillable phantoms directly from patient CT data. Methods: Liver, spleen, and kidney volumes were segmented from patient CT data. Each organ was converted to a shell and filling holes and leg supports were added using computer aided design software and prepared for printing. Additional fixtures were added to the liver to allow lesion inserts to be fixed within the structure. Phantoms were printed from an ultraviolet curable photopolymer using polyjet technology on an Objet EDEN 500V 3D printer. Results: The final print material is a clear solid acrylic plastic which is watertight, rigid, and sufficiently durable to withstand multiple assembly and scanning protocols. Initial scans of the phantoms have been performed with Tc‐99m SPECT and F‐18 PET/CT. Conclusions: The organ geometry showed good correspondence with anatomical references. The methodology developed can be generally applied to other anatomical or geometrical phantoms for molecular imaging.